1992
DOI: 10.1002/ppul.1950120405
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the CA 19‐9 antigen and lewis blood group with pulmonary disease severity in cystic fibrosis

Abstract: The altered carbohydrate structure of sputum from patients with cystic fibrosis (CF) has been thought to be due to the inflammatory airway response. Carcinoembryonic antigen (CEA) and CA 19-9 detect sialosylated carbohydrates in mucus. The epitope of CA 19-9 is part of the Lewis A (Le(a)) blood group antigen. Serum concentrations of CEA and CA 19-9 were determined by radioimmunoassay in 41 CF patients, aged 6-34 years; 16 were asymptomatic Outpatients, and 25 had been admitted for pulmonary exacerbations. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Other investigators have confirmed our findings (8). The present study extends these observations by demonstrating that even very young CF patients have elevated sialyl Le" levcls compared with serum antigen levels of normal babies or infants and young children who have lung diseases.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Other investigators have confirmed our findings (8). The present study extends these observations by demonstrating that even very young CF patients have elevated sialyl Le" levcls compared with serum antigen levels of normal babies or infants and young children who have lung diseases.…”
Section: Discussionsupporting
confidence: 80%
“…First, serum mucin from a single CF patient most resembled human lung mucin with respect to carbohydrate and amino acid composition (5). Second, serum sialyl Lea antigen levels correlated with measures of lung disease in two studies of groups of CF patients (7,8). Third, of 39 CF patients in the present study, 22 had some evidence of lung disease when their blood was drawn.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…antigen was originally used as a tumor marker in gastrointestinal malignancies. Increased serum CA 19-9 values have also been observed in CF patients [8][9][10], especially in those with progressive pulmonary disease [11]. However, it is not clear whether patients with mild disease and a borderline sweat test also have high levels.…”
Section: Introductionmentioning
confidence: 93%